Noninvasive in-vivo tracing and imaging of transplanted stem cells for liver regeneration. Issue 1 (December 2016) - Cen, Panpan; Chen, Jiajia; Hu, Chenxia; Fan, Linxiao; Wang, Jie; Li, Lanjuan
Abstract Terminal liver disease is a major cause of death globally. The only ultimate therapeutic approach is orthotopic liver transplant. Because of the innate defects of organ transplantation, stem cell-based therapy has emerged as an effective alternative, based on the capacity of stem cells for multilineage differentiation and their homing to injured sites. However, the disease etiology, cell type, timing of cellular graft, therapeutic dose, delivery route, and choice of endpoints have varied between studies, leading to different, even divergent, results. In-vivo cell imaging could therefore help us better understand the fate and behaviors of stem cells to optimize cell-based therapy for liver regeneration. The primary imaging techniques in preclinical or clinical studies have consisted of optical imaging, magnetic resonance imaging, radionuclide imaging, reporter gene imaging, and Y chromosome-based fluorescence in-situ hybridization imaging. More attention has been focused on developing new or modified imaging methods for longitudinal and high-efficiency tracing. Herein, we provide a descriptive overview of imaging modalities and discuss recent advances in the field of molecular imaging of intrahepatic stem cell grafts.